Incidence and severity of childhood pneumonia in the first year of life in a South African birth cohort: the Drakenstein Child Health Study. Issue 2 (February 2015) - le Roux, David M; Myer, Landon; Nicol, Mark P; Zar, Heather J
Summary: Background: Childhood pneumonia causes substantial mortality and morbidity. Accurate measurements of pneumonia incidence are scarce in low-income and middle-income countries, particularly after implementation of pneumococcal conjugate vaccine. We aimed to assess the incidence, severity, and risk factors for pneumonia in the first year of life in children enrolled in a South African birth cohort. Methods: This birth cohort study is being done at two sites in Paarl, a periurban area of South Africa. We enrolled pregnant women (>18 years) and followed up mother–infant pairs to 1 year of age. We obtained data for risk factors and respiratory symptoms. Children received 13-valent pneumococcal conjugate vaccine according to national immunisation schedules. We established pneumonia surveillance systems and documented episodes of ambulatory pneumonia and pneumonia warranting hospital admission. We calculated incidence rate ratios for pneumonia with mixed-effects Poisson regression. Findings: Between May 29, 2012 and May 31, 2014, we enrolled 697 infants who accrued 513 child-years of follow-up. We recorded 141 pneumonia episodes, with an incidence of 0·27 episodes per child-year (95% CI 0·23–0·32). 32 (23%) pneumonia cases were severe pneumonia, with an incidence of 0·06 episodes per child-year (95% CI 0·04–0·08). Two (1%) of 141 pneumonia episodes led to death from pneumonia. Maternal HIV, maternal smoking, male sex, and malnutrition were associated with an increased incidence of pneumonia. Interpretation: Pneumonia incidence was high in the first year of life, despite a strong immunisation programme including 13-valent pneumococcal conjugate vaccine. Incidence was associated with pneumonia risk factors that are amenable to interventions. Prevention of childhood pneumonia through public health interventions to address these risk factors should be strengthened. Funding: Bill & Melinda Gates Foundation, South African Thoracic Society, Federation of Infectious Diseases Societies of South Africa, and University of Cape Town.